2018
DOI: 10.2139/ssrn.3178972
|View full text |Cite
|
Sign up to set email alerts
|

Inflation and Stock Returns at B3

Abstract: We examine the impact of expected inflation on stock returns. We use inflation forecasts from the Focus survey and real returns of Ibovespa (the index of B3, the Brazilian stock exchange). In our main specification, an increase of 1 percentage point in expected inflation for the next 12 months is associated with a decline of 0.57 percentage points in stock returns. Stock returns react negatively to the 5-year CDS volatility and the VIX index. A simulated portfolio with a strategy based on changes in inflation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This contradicts Fama's (1981) argument which deduced a positive relationship between real stock returns and real activity, and a negative relationship between inflation and real activity, which when both relationships are combined yield a negative inflation-stock returns relation. These results are also inconsistent with several studies in both developed and developing countries such as in the United States (Fama, 1990), Brazil (Chaves and Silva, 2018), Malaysia (Rahman et al, 2009), Japan (Humpe and Macmillan, 2007), Canada, Spain, Switzerland (Ely and Robinson, 1997), Germany, Italy, United Kingdom (Nasseh and Strauss, 2000) and Australia (Paul and Mallik, 2003). Moreover, economic theory also states that stock returns and real activity should be positively related, implying that as industrial production increases in real terms, their net asset value should increase.…”
Section: Impact Of Industrial Production On Stock Returns and Inflationmentioning
confidence: 67%
See 2 more Smart Citations
“…This contradicts Fama's (1981) argument which deduced a positive relationship between real stock returns and real activity, and a negative relationship between inflation and real activity, which when both relationships are combined yield a negative inflation-stock returns relation. These results are also inconsistent with several studies in both developed and developing countries such as in the United States (Fama, 1990), Brazil (Chaves and Silva, 2018), Malaysia (Rahman et al, 2009), Japan (Humpe and Macmillan, 2007), Canada, Spain, Switzerland (Ely and Robinson, 1997), Germany, Italy, United Kingdom (Nasseh and Strauss, 2000) and Australia (Paul and Mallik, 2003). Moreover, economic theory also states that stock returns and real activity should be positively related, implying that as industrial production increases in real terms, their net asset value should increase.…”
Section: Impact Of Industrial Production On Stock Returns and Inflationmentioning
confidence: 67%
“…Furthermore, this implies that stock returns in Malta do not provide adequate protection against inflation and hence are not consistent with the Fisher (1930) hypothesis but are consistent with the findings of Erb et al (1995). Nonetheless, previous studies such as Fama and Schwert (1977), Gultekin (1983), Geetha et al (2011) and Chaves and Silva (2018), found a negative relationship in several developed and developing countries including Brazil, Germany, Italy, Malaysia, Switzerland, and US. This may be because of the time series methodology used.…”
Section: Variables Affecting Stock Returns Directlymentioning
confidence: 67%
See 1 more Smart Citation